Plant trait–digestibility relationships across management and climate gradients in permanent grasslands. Issue 5 (25th June 2014) - Gardarin, Antoine; Garnier, Éric; Carrère, Pascal; Cruz, Pablo; Andueza, Donato; Bonis, Anne; Colace, Marie‐Pascale; Dumont, Bertrand; Duru, Michel; Farruggia, Anne; Gaucherand, Stéphanie; Grigulis, Karl; et al.
Summary Dry matter digestibility is a critical component of herbage nutritive value, a major service delivered by grasslands. The aim of this study was to test whether the dominance hypothesis applies to assess the impacts of environmental gradients and management regimes on this component of herbage nutritive value in permanent grasslands. At the plant level, digestibility has been related to a number of functional traits, but whether this can be scaled up to the community level in species‐rich grasslands and how such relationships are modulated by environmental conditions and management regimes remain unknown. Our primary objective was to test whether community‐weighted means – species trait values weighted by the species abundance – of morphological, phenological and chemical traits could be used to explain variations in digestibility over a large range of climatic contexts, soil resource levels and management regimes. Our second objective was to explain variations in community digestibility within and among nine contrasting sites along large natural and man‐induced environmental gradients. Over the whole data set, digestibility and most community‐weighted means of traits responded to climatic factors and management regimes, but relations were not always significant when each site was considered separately. Community digestibility was significantly related to one or more plant traits within each site and to all of the measured traits when considering all the sites. Leaf dry matter content (LDMC) had the most consistent effects on digestibility, with a strikingly similar negative effect within each site. Potential evapotranspiration was negatively related to digestibility and contributed to explain a large part of the among‐site variance. In addition, a low return interval of disturbance and a high disturbance intensity (biomass removal) were both associated with a high digestibility. Synthesis and applications. Disturbance regime, plant traits and local climate impacted dry matter digestibility roughly equally in grasslands. The effects of community composition on digestibility and its response to abiotic factors could be successfully captured by community‐weighted means of leaf dry matter content. This functional marker can be used to develop indicators and grassland management rules to support farmers in the refinement of their practices towards specific needs, such as target production outputs.